DNA triplex-based fluorescence turn-on sensors for adenosine using a fluorescent molecular rotor 5-(3-methylbenzofuran-2-yl) deoxyuridine. Issue 8 (25th January 2019) - Kanamori, Takashi; Masaki, Yoshiaki; Oda, Yuki; Ohzeki, Hiroki; Ohkubo, Akihiro; Sekine, Mitsuo; Seio, Kohji
Abstract : Fluorescence turn-on detection of adenosine based on microenvironmental and conformational changes of a fluorescent molecular rotor in the DNA triplex is reported. Abstract : Fluorescence turn-on sensors for adenosine were developed using DNA triplexes modified with a fluorescent molecular rotor 5-(3-methylbenzofuran-2-yl)deoxyuridine (dU MBF ) and abasic sites. Binding of adenosine to the abasic site next to the dU MBF changed the microenvironment and conformation (from the twisted to planar state) of dU MBF and enhanced the fluorescence. Adenosine could be selectively detected over other nucleosides and adenosine phosphates. The binding of adenosine was confirmed by UV-thermal melting experiments. Further, the conformational changes of dU MBF from the twisted to coplanar state upon binding of adenosine was supported by MD simulations.